Strategi Pembelajaran IPA yang Menarik untuk Siswa SD di Era Digital - Adrias Adrias; Anihsa Anihsa; Citra Amelia; Salmaini Safitri Syam (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This research discusses interesting Natural Sciences (IPA) learning strategies for elementary school students in the digital era. With the development of technology, the use of digital media such as animated videos, learning applications, and 3D simulations has become an effective solution in improving students' understanding of science concepts. The research method used is a literature study by analyzing various literature related to the application of technology in science learning. The results of the study show that the integration of digital media can increase students' learning motivation as well as learning effectiveness. However, challenges such as limited infrastructure and teacher readiness are still obstacles in its implementation. Therefore, training for educators and facility support is needed so that the use of digital technology in science learning can run optimally.